Pengaturan Putaran Dua Motor Stepper Melalui LPT1 - Riyanto Riyanto; Yuneli Wikundhari (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2009)
Existence of complication various industrial electronic system cause to go down the result of industry. Here in after, intention of this final project is visual language application of basic for the application at a band conveyor system industrial or factory so that water down in control of produced goods. Here visual language of basic used as control instruct rotation from stepper motor [pass/through] a PC. Here used PC only one, this matter because of to be more performance efficiency from the system easier so that in the case of observation and also control.